FEATURES OF DISTRIBUTION OF TRACE ELEMENTS IN SOILS OF BACKGROUND AND IMPACT ZONES IN DIAMOND MINING AREAS IN THE NORTHWEST OF THE SIBERIAN PLATFORM - Yana B. Legostaeva; Anna G. Gololobova (Известия Томского политехнического университета: Инжиниринг георесурсов, 2021)
The study relevance is caused by the intensive development of the mining industry in the study area, during which the environment is polluted with chemical substances in the conditions of the spread of permafrost. First, this is soil pollution with pollutants, which remain in the soil for many years, even after removing pollution sources. Therefore, this study makes it possible to identify the geochemical specificity of soils under the influence of anthropogenic activity. The main aim: study of the elemental composition and their vertical distribution in the permafrost soils of North-West Yakutia exposed to technogenic impact in the conditions of diamond mining. Objects and Methods. This article presents the results of the work performed for the period from 1994 to 2019 on the territory of the Daldyn kimberlite field, where the kimberlite pipes Udachnaya and Zarnitsa are being mined, and where the Udachny mining and processing plant of AK Alrosa (PJSC) is located. The object of study is the permafrost soils of the north-taiga landscapes of North-West Yakutia. The soils of this region reflect the general patterns of soil cover formation in the study area. They are part of the East Siberian permafrost-northern taiga region of the boreal soil belt of Russia. In field observations, a profile approach was applied, involving the collection of samples from all soil genetic horizons to the boundary of the seasonally thawed layer. The sign contents of 23 chemical elements were determined by the method of spectral-semiquantitative analysis. Results. The geochemical studies of permafrost soils on the territory of the Udachninsky mining and processing plant are presented. To characterize the geochemical environment of soils, the coefficient of technogenic concentration (Kc) and the coefficient of accumulation (K0–К3) of the studied elements were calculated. Accumulative series reflecting the geochemical specifics of the study area were built. Each of the studied soil types is characterized by the originality of the microelement spectrum. Polyelement associations are created as a result of the geochemical influence of the soil-forming substrate. It was revealed that the territory of the Daldyn-Alakit region is characterized by increased concentrations of Cr, Ni, Co, V, Cu, Pb, Li, Sr in soils.